2011
DOI: 10.3928/01484834-20111017-01
|View full text |Cite
|
Sign up to set email alerts
|

Team-Based Learning: Systematic Research Review

Abstract: Team-based learning (TBL) is an active learning method developed to help students achieve course objectives while learning how to function in teams. Many faculty members have adopted TBL because it is a unique teaching method, but evidence about its effectiveness is unclear. Seventeen original studies on TBL are presented in this systematic review of research. The studies include descriptive, explanatory, and experimental research published from 2003 to 2011 in the nursing, medical, education, and business lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
142
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 21 publications
10
142
0
13
Order By: Relevance
“…Our study confirmed previously published outcomes of enhanced engagement and satisfaction with learning activities, increased selfdirected learning, and high acceptance rate of TBL compared to traditional lectures (Sisk 2011;Rezaee and Mosalanejad 2015). Prior resident exposure to TBL was highly variable and did not seem to affect the outcomes and acceptance rate of TBL.…”
Section: Discussionsupporting
confidence: 80%
“…Our study confirmed previously published outcomes of enhanced engagement and satisfaction with learning activities, increased selfdirected learning, and high acceptance rate of TBL compared to traditional lectures (Sisk 2011;Rezaee and Mosalanejad 2015). Prior resident exposure to TBL was highly variable and did not seem to affect the outcomes and acceptance rate of TBL.…”
Section: Discussionsupporting
confidence: 80%
“…Research suggests that the use of TBL can help improve student performance (Zingone et al, 2010) and increase student engagement, as well as satisfaction (Chung, Rhee, Baik, & A, 2009;Clark, Nguyen, Bray, & Levine, 2008;Haidet, O'Malley, & Richards, 2002;Sisk, 2011). TBL has been suggested as a new model of education for nursing (Clark et al, 2008;Sisk, 2011) that helps meet the call to transform nursing education by creating an engaging learning environment for students (Mennenga & Smyer, 2010).…”
Section: Team-based Learning and Ethics Education In Nursingmentioning
confidence: 99%
“…However, with some minor modifications, this approach can be adapted for use in teaching more abstract courses, such as applied health care ethics (Chung et al, 2009). TBL helps students learn how to work through challenging ethical dilemmas in a group setting akin to a health care team (Sisk, 2011), which is an especially critical skill when there is disagreement about the best course of action and no clear right or wrong answer (Hamric, 2001). This experience facilitates the development of interpersonal and team skills necessary to work through potentially emotionally charged clinical situations (Clark et al, 2008).…”
Section: Team-based Learning and Ethics Education In Nursingmentioning
confidence: 99%
“…The students highlight the importance of a less competitive, more collaborative culture. Such attributes have been discussed in relation to problem-based learning and related theories [9,[27][28][29] . The body of literature around critical thinking has also indicated the importance of personal reflection and discussion in groups to grasp complex and practice-related issues [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%